Interpretation of the Authority of Services and Agencies in the Regional Government Structure - Syahril, Syahril (Asosiasi Ide Bahasa Kepri, 2023)
This article aims to clarify the interpretation of the authority of two nomenclatures of regional apparatus, namely regional services and regional bodies, in order to make it easier for regional governments to group government structures in their regions more accurately. The interpretation of the authority of Departments and Agencies in the regional government structure is related to the assignment of certain tasks and responsibilities to these institutions to carry out technical and administrative functions in accordance with their respective fields. This aims to create efficiency in the administration of regional government and ensure that each institution has a clear role and is in accordance with its expertise and duties. The research method applied is a normative juridical method with a conceptual approach. The research results show indications of differences between departments and agencies, which have significantly different functions and authorities; Regional services act as implementers of government affairs in the region, while regional bodies function as supporters of government affairs in the region.